Selecting and Using Course Readings: A Study of Instructors’ and Students’ Practices - Bischoping, Katerine (Canadian Journal of Higher Education, 2003)
University students’ practices of reading required course materials have rarely been studied systematically outside the laboratory and are given short shrift in course evaluation questionnaires. This study exam- ines, first, the reasons why a sample of instructors at a large university create selections of course readings and the factors, both pedagogical and otherwise, that influence their selections. Second, students’ patterns of reading in these instructors’ courses are studied to determine how they vary with the quantity of assigned readings, time of year, and the provision of systematic student feedback to instructors. Third, the most prevalent themes in student feedback about readings are explored, in tan- dem with instructors’ proposals about how to revise their reading selec- tions or teaching strategies.